PCR detection of Mycobacterium ulcerans—significance for clinical practice and epidemiology. (2nd December 2018) - Bretzel, Gisela; Beissner, Marcus
ABSTRACT: Introduction : Buruli ulcer (BU) is a neglected disease which has been reported from mostly impoverished, remote rural areas from 35 countries worldwide. BU affects skin, subcutaneous tissue, and bones, and may cause massive tissue destruction and life-long disabilities if not diagnosed and treated early. Without laboratory confirmation diagnostic and treatment errors may occur. This review describes the application of IS 2404 PCR, the preferred diagnostic test, in the area of individual patient management and clinico-epidemiological studies. Areas covered : A Medline search included publications on clinical sample collection, DNA extraction, and PCR detection formats of the past and present, potential and limitations of clinical application, as well as clinico-epidemiological studies. Expert commentary : A global network of reference laboratories basically provides the possibility for PCR confirmation of 70% of all BU cases worldwide as requested by the WHO. Keeping laboratory confirmation on a constant level requires continuous outreach activities. Among the potential measures to maintain sustainability of laboratory confirmation and outreach activities are decentralized or mobile diagnostics available at point of care, such as IS 2404 -based LAMP, which complement the standard IS 2404 -based diagnostic tools available at central level.